2017
DOI: 10.17265/2328-7136/2017.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Plasma Exosome Concentrations in Healthy Male Individuals

Abstract: Exosomes are nanometer sized vesicles (30-100 nm), released from cells following the fusion of multivesicular bodies with the plasma membrane. Exosomes have a major role in intracellular communication, immune response modulation, physiological and pathological functions, and an important use in different drug therapies. Moreover, they have been identified as potential biomarkers and are involved in cancer and many other disease processes. Despite the developments in this area, no studies exist that assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…We also found that, in placebo-assigned participants (Table 2 and Supplementary Figures 2 and 3), the concentration and phosphoprotein content of plasma neuronal-enriched EVs remained relatively stable over time, as previously shown for total plasma EVs [40], suggesting that circulating neuronal-enriched EVs in individual humans demonstrate a unique signature that remains stable over time. In addition, several studies have established the stability of EVs during storage and their resistance to a limited number of freeze-thaw cycles [41, 42], whereas EV phosphoproteins remain stable over 5 years in storage [43] suggesting that EV biomarkers may reflect the phosphoprotein status in their cells of origin even after years in storage. The presence of intracellular mediators that belong to a common cascade in different phosphorylated states raises the possibility that the status of signaling cascade in the parent cells may be interrogated using circulating EVs.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that, in placebo-assigned participants (Table 2 and Supplementary Figures 2 and 3), the concentration and phosphoprotein content of plasma neuronal-enriched EVs remained relatively stable over time, as previously shown for total plasma EVs [40], suggesting that circulating neuronal-enriched EVs in individual humans demonstrate a unique signature that remains stable over time. In addition, several studies have established the stability of EVs during storage and their resistance to a limited number of freeze-thaw cycles [41, 42], whereas EV phosphoproteins remain stable over 5 years in storage [43] suggesting that EV biomarkers may reflect the phosphoprotein status in their cells of origin even after years in storage. The presence of intracellular mediators that belong to a common cascade in different phosphorylated states raises the possibility that the status of signaling cascade in the parent cells may be interrogated using circulating EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the translation of a research-grade cell culturing process into a scalable, clinical-grade protocol is expensive, time-consuming, and vulnerable to contamination [58]. Therefore, the use of biological fluids, such as plasma or serum, as alternative sources, offers undeniable advantages [56]: (i) they are particularly enriched with EVs, reaching 1–5 × 10 8 vesicles/mL, even if the yield depends on the isolation protocol adopted [59]; (ii) plasma and serum are “ready to use” and “cheap” sources, allowing to obtain a huge amount of vesicles without the need of setting up in vitro cell cultures; (iii) EV isolation can be realized with an autologous procedure (the patient’s own blood can be used), a more advisable choice to prevent immune-mediated adverse reactions. In the case of patients debilitated by severe diseases or under chemotherapy regimens, fresh frozen plasma (FFP) from compatible healthy donors could be used as a clinical translational source for vesicle isolation.…”
Section: Plasma-derived Evsmentioning
confidence: 99%
“…Therefore, Abu-Seer evaluated the reliability of plasma EV testing. [218] In this experiment, EV reliability was evaluated in three aspects: 1) within-day reliability, which is to assess the repeatability of plasma-EV measurement results in one day at different points in time (i.e., 1, 2, 3, 4, 5, 6, 8, and 10 h); 2) between-day reliability, which is to assess the repeatability of plasma EV measurement results between multiple days (five times over five consecutive days); and 3) EV stability between freezing and fresh plasma samples. The measurements of EV concentrations and size distributions displayed good withinday reliability and between-day reliability.…”
Section: Challengesmentioning
confidence: 99%